New Advances in the Regulation of Leaf Senescence by Classical and Peptide Hormones - Huang, Peixin; Li, Zhonghai; Guo, Hongwei (Frontiers in Plant Science, 2022)
Leaf senescence is the last stage of leaf development, manifested by leaf yellowing due to the loss of chlorophyll, along with the degradation of macromolecules and facilitates nutrients translocation from the sink to the source tissues, which is essential for the plants’ fitness. Leaf senescence is controlled by a sophisticated genetic network that has been revealed through the study of the molecular mechanisms of hundreds of senescence-associated genes (SAGs), which are involved in multiple layers of regulation. Leaf senescence is primarily regulated by plant age, but also influenced by a variety of factors, including phytohormones and environmental stimuli. Phytohormones, as important signaling molecules in plant, contribute to the onset and progression of leaf senescence. Recently, peptide hormones have been reported to be involved in the regulation of leaf senescence, enriching the significance of signaling molecules in controlling leaf senescence. This review summarizes recent advances in the regulation of leaf senescence by classical and peptide hormones, aiming to better understand the coordinated network of different pathways during leaf senescence.